Ratios of multijet Cross Sections in p p collisions at radical(s) = 1.8 TeV. - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Alves, G; Amos, N; Anderson, E; Baarmand, M; Babintsev, V; Babukhadia, L; et al. (2001)
We report on a study of the ratio of inclusive three-jet to inclusive two-jet production cross sections as a function of total transverse energy in pandpmacr; collisions at a center-of-mass energy sqrt[s] = 1.8 TeV, using data collected with the D0 detector during the 1992-1993 run of the Fermilab Tevatron Collider. The measurements are used to deduce preferred renormalization scales in perturbative O(alpha(3)(s)) QCD calculations in modeling soft-jet emission.